Effect of individual physiotherapy and telerehabilitation on back pain and quality of life in people with multiple sclerosis with mild and moderate disability - Knapova, Veronika; Grosserova, Barbora; Vetrovska, Renata; Uher, Tomas; Novotna, Klara (Multiple sclerosis and related disorders, 2025)
BACKGROUND: Back pain is a common but often underestimated symptom of patients with MS that can negatively influence their quality of life. However there are only limited number of studies comparing the effect of different types of exercise and use of telerehabilitation on back pain in MS. Therefore, the aim of the study is to compare whether telerehabilitation alone is as effective as conventional outpatient physiotherapy followed by online exercise. METHODS: This single-centre intervention study compared the impact of different individual outpatient physiotherapy treatments (Group 1 - individual Pilates exercise or Group 2 - strength training) and telerehabilitation alone (individual Pilates exercise with a physiotherapist online). The primary objective was to compare the effect of interventions on back pain (assessed using the Visual Analogue Scale and McGill Pain Questionnaire) and quality of life (Multiple Sclerosis Quality of Life-54). Secondary aims were to compare effect of interventions on spine and thorax mobility, functional mobility (assessed using the Timed 25 foot walk test, Six Spot Step test), respiratory muscle strenght and patient reported outcomes (assessed using he Hospital Anxiety and Depression Scale, Fatigue Severity Scale). RESULTS: 45 people with MS were enrolled in the study (3 men, age:48.4± SD 11,5, Expanded Disability Status Scale (EDSS): 3.3±SD 1,1) and 36 people completed the entire exercise program. All types of exercise intervention showed a positive effect on the reduction of back pain, quality of life and fatigue. The interventions also increased respiratory muscle strength and increased thorax mobility, but we did not find any effect of interventions on gait tests. There were no difference in effect on outcome measures between different types of exercise interventions. CONCLUSION: Telerehabilitation, involving individual exercise sessions with a physiotherapist, has a comparable effect on reducing back pain, improving quality of life, and enhancing respiratory muscle strength in people with MS as individual Pilates or strength training.
Keywords: lidé; Middle Aged; Adult; Multiple sclerosis; Back Pain; Back pain; stupeň závažnosti nemoci; Multiple Sclerosis; techniky fyzikální terapie; Female; Physiotherapy; telerehabilitace; Quality of Life; Pilates; Humans; Telerehabilitation; roztroušená skleróza; lidé středního věku; Resistence training; mužské pohlaví; Exercise Therapy; ženské pohlaví; Severity of Illness Index; terapie cvičením; kvalita života; Male; dospělí; bolesti zad; Physical Therapy Modalities